2202. The Hepatitis C Virus Cascade of Care at Stony Brook University Hospital: Risk Factors for Linkage to Care. (26th November 2018) - Lier, Audun; Smith, Kalie; Bronson, Silvia; Khoo, Teresa; Odekon, Kerim; Abeles, Ruth; Patel, Pruthvi; Kelly, Gerald; Tharakan, Mathew; Soliman, Manal; Fries, Bettina C; Marcos, Luis A
Abstract: Background: Huge efforts are being made to screen high-risk populations for Hepatitis C virus (HCV) infection, however linkage to care (LTC) rates remain low. The aim of this study was to assess the factors affecting LTC among HCV positives in a major tertiary academic medical center in eastern New York. Methods: A retrospective chart review was performed on all patients with ICD-9 or 10 diagnostic codes for HCV positive antibody over a period of 2 years (2016–2017) at Stony Brook Medicine. Data were collected for HCV RNA, LTC, demographics, type of insurance, employment status, psychiatric diagnosis, comorbidities, HIV or HBV coinfections, substance use disorder, and level of fibrosis. Univariate and multivariate analyses were performed to find associated factors with LTC. Results: A total of 600 cases (62.6% male; 74% White; median age: 59 years) had a positive HCV antibody, 264 (44.4%) had a positive follow-up HCV RNA test and 138 (52.2%) were LTC. The average time for LTC was 1.5 months (50 days; interquartile range 21–121). In the univariate analysis, the following factors were significantly associated with LTC: older age (OR 1.022), having medicaid (OR 0.421), people who inject drugs (PWID) (OR 0.216), cocaine and marijuana use (OR 0.457), polysubstance use (OR 0.311), having a primary care provider (OR 2.290) and being a baby boomer (OR 1.718). The vast majority of patients came from three zip codes within south central Suffolk County, coinciding with the highest prevalence of heroin use. Conclusion: In this population insurance type, younger age and substance use (injection drugs, marijuana, cocaine, polysubstance) were associated with lower odds of LTC. Having a primary care provider and being a baby boomer were the only two independent risk factors associated with increased odds of LTC. Due to an increased number of HCV cases in younger populations, particularly PWID, further outreach efforts are urgently needed to spread HCV screening awareness and increase testing in high prevalence areas. Disclosures: All authors: No reported disclosures.